2016
DOI: 10.21746/aps.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of in vitro regeneration protocol for a popular Indica rice (Oryza sativa L. cv Swarna)

Abstract: Though regeneration system in rice has been very well established compare to other crop plants, the fact remains that, most of the indica rice varieties are still recalcitrant for regeneration and genetic transformation. Therefore, refinement of tissue culture protocol for generation of embryogenic calli and regeneration of the fertile plants from a single cell should be a pre requisite event for development of transgenic plants. Here, in this study we reported high frequency robust regeneration protocols for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…Our results are in agreement with those reported by Sah et al (2014) who demonstrated the advantage of phytagel over agar for callus induction frequency in rice (using the Kitaake cultivar). Juturu et al (2016) also found that medium solidified with phytagel gave 30% higher callus fresh weight using the Swarna rice cultivar. In addition to phytagel, gelrite was found to show higher efficiency for callus induction as compared to agar using Swarna and Mahsuri rice cultivars ( Jadhav et al, 2011 ).…”
Section: Discussionmentioning
confidence: 87%
“…Our results are in agreement with those reported by Sah et al (2014) who demonstrated the advantage of phytagel over agar for callus induction frequency in rice (using the Kitaake cultivar). Juturu et al (2016) also found that medium solidified with phytagel gave 30% higher callus fresh weight using the Swarna rice cultivar. In addition to phytagel, gelrite was found to show higher efficiency for callus induction as compared to agar using Swarna and Mahsuri rice cultivars ( Jadhav et al, 2011 ).…”
Section: Discussionmentioning
confidence: 87%
“…High percentage of re-generable embryogenic calli is a prerequisite for genetic manipulation towards varietal improvement [55]. This study aimed to test and improve the embryogenic potential of calli for better plant regeneration efficiency.…”
Section: Callus Inductionmentioning
confidence: 99%
“…The high percentage of re-generable embryogenic calli is a prerequisite for genetic manipulation towards varietal improvement. This study aimed to test and improve the embryogenic potential of calli for better plant regeneration e ciency (Juturu et al 2016). Flower and boll number is an important trait for upland cotton.…”
Section: Discussionmentioning
confidence: 99%
“…The highest callus induction was observed in shoot tip tissue and this is possibly due to the presence of meristematic cells at the tip end of the seedling in Gossypium hirsutum. It was reported that high percentage of re-generable embryogenic calli is a prerequisite for genetic manipulation towards varietal improvement (Juturu et al, 2016). Embryogenic callus is best requirement for successful tissues regeneration.…”
Section: Discussionmentioning
confidence: 99%